Pelaksanaan Visi dan Misi Sekolah dalam Mewujudkan Kegiatan Belajar-Mengajar Di SDLBN Kedungkandang Malang - Galan Suswardana (VOCAT: JURNAL PENDIDIKAN KATOLIK, 2022)
This research focuses on the school’s vision and mission in achieving teaching and learning activities in special education elementary school in Kedungkandang. Researchers argued that the implementation of the school’s vision and mission is very important in learning activities. Every school has a purpose to be reached. A school is not only a place for transferring knowledge from the teachers to the students, but the school is also a knowledge internalization for the students and the teachers in developing their life. This is supported by the opinion of an Indonesian education expert, Ki Hajar Dewantara, who said that schools are parks, parks do not scare children, but parks are fun places for learning. It states that school is a fun place where everyone feels free to absorb the knowledge that he/ she has gained and the individual can express himself at the same time. Each individual can learn how to count, read, moral, and art as well as each individual get the greatest opportunity to create his own world through what he/ she learns. Based on that opinion, the researcher concludes that the implementation of the school's vision and mission will determine the direction of education to be achieved. Therefore, phenomenological analysis is needed to analyse the vision and mission applied at Kedungkandang Special Education Elementary School in realizing teaching and learning activities in which the students are children with difable.